Efficacy of Hongjing I granule, an herbal medicine, in patients with mild to moderate erectile dysfunction in a randomized controlled trial - Xu, Run-Nan; Guo, Jun; Zhang, Chun-He; Zhou, Qing; Gen, Qiang; Wang, Fu; Zhao, Yu; Luo, Xin-Yun; Li, Yan-Feng; Fu, Yi-Jia; Zhang, Xin; Wang, Wen-Zhi; et al. (Frontiers in Pharmacology, 2024)
BackgroundHJIG is a potential treatment for erectile dysfunction (ED) that has been used in China for over 20 years. We conducted a multi-center, double-blind, randomized, placebo-controlled trial to evaluate the effectiveness and safety of the Chinese Herbal Medicine, Hongjing I granule (HJIG), in patients with mild to moderate erectile dysfunction (ED).MethodsThis study is structured as a randomized, double-blind, placebo-controlled trial, executed across multiple centers. The recruitment strategy is primarily oriented towards patients demonstrating a pronounced preference for solely leveraging traditional Chinese medicine (TCM) interventions, a preference that is widely observed within TCM healthcare settings. A total of 100 patients, presenting with mild to moderate ED, specifically linked to the traditional diagnostic criteria of qi deficiency and blood stasis, will be enrolled. These participants will be randomly distributed between the HJIG (N = 50) and placebo (N = 50) arms. The designated treatment period is set at 8 weeks. Primary outcome measures encompass the International Index of Erectile Function-Erectile Function domain (IIEF-EF) score, the Sexual Encounter Profile (SEP), and scores derived from the traditional Chinese medicine symptom evaluation.ResultsOf the 122 men enrolled, the baseline IIEF-EF score averaged 16.00 [IQR: 13.00, 18.00]. Eight weeks post-randomization, the HJIG group demonstrated a mean change in IIEF-EF scores of 7.80 (±3.25), compared to 3.33 (±3.90) in the placebo group, signifying a marked difference (P < 0.001). The median alterations in SEP3 scores were 0.50 [IQR: 0.36, 0.75] for the HJIG group and 0.50 [0.20, 0.67] for the placebo group, revealing a statistically relevant distinction (P = 0.05). In both primary outcomes, HJIG proved superior to the placebo. Additionally, improvements in TCM symptom scores were notably greater in the HJIG group relative to the placebo, with no adverse events reported across both groups.ConclusionThe Hongjing I granule significantly improved symptoms in patients with mild to moderate ED. However, to validate these findings, further extended randomized trials are warranted.Clinical Trial RegistrationThe study has been registered in the Chinese Clinical Trial Registry (ChiCTR) and the registration number was ChiCTR2000041127.